Case report: The first description of a thyroglossal duct cyst in a hen (Gallus gallus domesticus) - Pop, Romelia; Oren, Stephanie; Negoescu, Andrada; Cătoi, Cornel; Tăbăran, Alexandru-Flaviu (Frontiers in Veterinary Science, 2024)
Thyroglossal duct cyst represents a congenital anomaly of the cervical region, rarely documented in animals. Although previously reported in dogs, cats, horses, goats, pigs, and calves, never in birds. This report describes a rare case of thyroglossal duct cyst in a hen. A necropsyautopsy of a Transylvanian Naked Neck hen carried following diphtheroid mucocutaneous lesions. The necropsyautopsy revealed a large, cyst-like structure measuring 0.5 cm at the level of the caudal edge of the left thyroid gland. Histologically, the cystic mass, bordered by 1-2 lines of well-differentiated ciliated cuboidal cells, presented nuclear immunoreactivity for Thyroid transcription factor 1. To the best authors' knowledge, there are no previous records. There are no previous records of thyroglossal duct cysts in avians. Moreover, this is the first case describing a thyroglossal duct cyst in a hen.